Static stretching of the hamstrings muscle for injury prevention in football codes: a systematic review - Rogan, S.; Wüst, D.; Schwitter, T.; Schmidtbleicher, D. (Asian Journal of Sports Medicine, 2013)
Purpose: Hamstring injuries are common among football players. There is still disagreement regarding prevention. The aim of this review is to determine whether static stretching reduces hamstring injuries in football codes. Methods: A systematic literature search was conducted on the online databases PubMed, PEDro, Cochrane, Web of Science, Bisp and Clinical Trial register. Study results were presented descriptively and the quality of the studies assessed were based on Cochrane`s `risk of bias` tool. Results: The review identified 35 studies, including four analysis studies. These studies show deficiencies in the quality of study designs. Conclusion: The study protocols are varied in terms of the length of intervention and follow-up. No RCT studies are available, however, RCT studies should be conducted in the near future.